Infections in the maxillofacial region in the clinic material – retrospective analysis - Wróbel-Roztropiński, Artur; Zagacki, Dawid; Kruczykowska, Lidia; Kozakiewicz, Marcin (Journal of Education, Health and Sport, 2022)
Infections in the maxillofacial and neck region are a serious problem nowadays. Lately diagnosed infection may lead to many hazardous complications including spreading through superior thoracic aperture to the mediastinum. That affects everyday life of patients, including his ability to work. The aim of this study was to analyze the factors affecting work inability associated with the treatment of maxillofacial and neck infections. We made a retrospective analysis of medical documentation of patients treated in our Department due to the infections of maxillofacial and neck region. In our research, mostly men were burden with infections in the maxilliofacial region and neck (64.3%). Patient presented poor oral hygiene thus the main cause of the infection was periodontal. Treatment period (including hospitalization and inability to work) varied from 1 up to 124 days; Mostly affected are patients in their 3rd and 4th decade of life when they are professionally active. A proper treatment (including surgical and pharmacological) is required to allow those patients come back to their everyday life.